Long-Term Quality of Life Results of Intrastromal Corneal Ring Segment Implantation in Keratoconus Patients Using the National Eye Institute Visual Function Questionnaire - Ayşegül Penbe; Işıl Kutlutürk Karagöz; Anıl Kubaloğlu; Esin Söğütlü Sarı (Southern Clinics of Istanbul Eurasia, 2018)
INTRODUCTION[|]The aim of this study was to investigate the long-term quality of life and vision level of keratoconus patients who underwent implantation of intrastromal corneal ring segments (ICRS).[¤]METHODS[|]During February 2012, 23 keratoconus patients that had ICRS implanted were included in this retrospective study. The patients were divided into 3 severity subgroups. After 4 years, uncorrected visual acuity (UCVA), best spectacle-corrected visual acuity (BCVA) and Kmax values were recorded. A Turkish version of the National Eye Institute Visual Function Questionnaire 25 (NEI-VFQ 25) was administered to all of the patients retrospectively.[¤]RESULTS[|]There was a notable increase in all patients' BCVA (p=0.001) and UCVA (p=0.021). The Kmax values were reduced in all cases (p=0.01); however, this reduction was not statistically significant in subgroup 2 (p=0.285). The peripheral vision score was also lower in type 2 (p=0.049). A significant correlation was found between BCVA/UCVA and NEI-VFQ 25 scores, except for general health, social functioning, general vision, dependency, and driving.[¤]DISCUSSION AND CONCLUSION[|]Patients' quality of life and vision scores support ICRS implantation as an acceptable option before penetrating keratoplasty for keratoconus treatment. But, the satisfaction and vision levels were not better in patients in the early stages of keratoconus. So it may be considered that early treatment of ICRS implantation is not a necessary protocol.[¤]